Early congenital syphilis with isolated bone involvement: a case report - Armangil, Didem; Canpolat, Fuat Emre; Yiğit, Sule; Demir, Haci Ahmet; Ceyhan, Mehmet (The Turkish Journal of Pediatrics, 2009)
Congenital syphilis is the oldest recognized congenital infection and still represents a serious healthcare problem in the 21st century. It is important to be fully informed regarding the early diagnosis and treatment of congenital syphilis to prevent its devastating complications leading to death. In this manuscript, we report a newborn infant with unusual clinical findings of congenital syphilis such as a non-fluctuant mass surrounding the left calf. She did not have any additional system involvement such as hepatic or skin involvement or lymph nodes. To our best knowledge, there are only a few case reports presented with isolated bone involvement. This case demonstrates that congenital syphilis should be considered in neonates with bone fractures, lytic bone lesions and periostitis.